SUSTAINABLE LOW POWER SENSOR NETWORKS FOR DISASTER MANAGEMENT - Kamel, Khaled; Smys (IRO Journal on Sustainable Wireless Systems, 2019)
The wireless sensor networks that framed using the tiny sensors that are very efficient in monitoring and conveying the information's that are sensed are almost engaged in a wide range of applications with the from environment monitoring to health monitoring. The conventional wireless sensor in spite of its sensing capabilities requires lot of power to operate which in return reduces the life time of the sensors. This paves a way for the low power wireless sensor networks that brings downs the energy consumption, by setting limit on the modes of the device operation. The paper uses the low power wireless devices for the management of a manmade disaster situation such as the air pollution created by the vehicle movement in the cities. The system acts as an early warning for metro cities, with heavy vehicle flow, the industrial outcomes and the other causes that emits the poisonous gas polluting the environment. The proposed system with the low power wireless sensor networks is tested over a busy are to evince the system in terms of the battery lifetime of the system and its monitoring capability.
Keywords: wireless sensor networks; disaster management; sustainability; low power wireless sensors; air pollution monitoring